Increased expression of prokineticin 2 and its receptor in endometrium of recurrent implantation failure patients decreased the expression of MMP9 important for decidualization - Jun Zhai; Linna Ma; Ziyin Chang; Ting Yu (BMC, 2022)
Abstract Background Studies have shown that abnormalities in the decidualization process were closely related to recurrent implantation failure (RIF). Prokineticin 2 (PK2) is a secreted protein with angiogenic and tissue remodeling functions but its role in the endometrium is unknown. Methods PK2 levels and its receptor PKR1 mRNA and protein levels in mid-secretory endometrium from normal and RIF women were examined by real-time PCR and western blotting, respectively. The effects of PK2 were evaluated by overexpressed PK2 in immortalized endometrial T-HESC cells using lentivirus vector and found different expression of Matrix metalloproteinase 9(MMP9) and lncRNA LUCAT1 by RNA-sequencing. The ability of PK2 to regulate LUCAT1 and MMP9 was verified in endometrial cells by real-time PCR and western blotting. Results Using endometrial biopsies from normal and RIF patients, we found increased expression of PK2, together with its receptor PKR1 in RIF patients. We then overexpressed PK2 in immortalized endometrial T-HESC cells using lentivirus vector and found decreased expression of Matrix metalloproteinase 9(MMP9), and increased expression of lncRNA LUCAT1. We verified the ability of PK2 to stimulate LUCAT1 and decrease MMP9 in endometrial cells. We further demonstrated that increased expression of a long noncoding RNA LUCAT1 and decreased expression of MMP9 in endometrial biopsies of patients with RIF. Thus, we highlighted the important role of PK2 and its receptor PKR1 in decidualization and RIF. Conclusion Prokineticin 2 and its receptor are important in endometrium decidualization. PK2 may affect endometrial decidualization through the LUCAT1- MMP9 pathway, thereby affecting embryo implantation.